Fatigue life assessment of welded joints by two local stress approaches: The notch stress approach and the peak stress method. (May 2018) - Bertini, Leonardo; Frendo, Francesco; Marulo, Giuseppe
Highlights: The fatigue life assessment of welded joints is investigated by different local methods. Specimens with different geometry were considered in the database. Tests were analysed by the notch stress approach and by the peak stress method. The effectiveness of the methods is discussed based on the scatter of results. The ease of use of the analysed methods is discussed in relation to geometry complexity. Abstract: This paper presents a comparison between two local methods that can be used for the fatigue life assessment of welded joints: the notch stress approach and the peak stress method. Even if they have been derived starting from entirely different theoretical backgrounds, both methods are based on the evaluation of a local stress acting at the notch tip of the seam weld, which is usually obtained through a finite element simulation. Said methods are applied to a collection of experimental data from three kinds of welded joints, which are characterized by different geometric parameters and, in particular, by a wide range of the element thickness. A total of 177 experimental tests are evaluated in this investigation, 31 of which are taken from literature while the other 152 are published here for the first time. The performance of the two methods is discussed in terms of the statistical dispersion in the analysed data. This is accomplished comparing the scatter bands obtained from a regression procedure in the S-N plot. In addition, some practical aspects related to the implementation of both methods are discussed, with particular attention to the ease of use offered, considering that this may represent a relevant aspect for the method's diffusion in practical applications.